Students’ Ability at Changing Direct into Indirect Speech and Indirect into Direct Speech - Muhammad Dalimunte; Maryati Salmiah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
Reported speech is one of difficult topics in learning English grammar, especially in changing the form from direct into indirect or reverse. Descriptive quantitative was used to find out the students’ ability in changing direct into indirect speech and reverse. There were five sentences that were changed by the students for two kinds of test. First, the test consisted of five direct sentences and the second, it consisted five indirect sentences.  As the conclusion of the students’ answers, the students found difficulties in changing those two kinds of sentences.